Persistence and activation of malaria hypnozoites in long-term primary hepatocyte cultures - Dembele,L; Franetich,J-F; Lorthiois,A; Gego,A; Zeeman,A-M; Kocken,CHM; Le,Grand R; Dereuddre-Bosquet,N; van,Gemert G-J; Sauerwein,R; Vaillant,J-C; Hannoun,L; et al. (Nature Medicine, 2014)
Malaria relapses, resulting from the activation of quiescent hepatic hypnozoites of Plasmodium vivax and Plasmodium ovale, hinder global efforts to control and eliminate malaria. As primaquine, the only drug capable of eliminating hypnozoites, is unsuitable for mass administration, an alternative drug is needed urgently. Currently, analyses of hypnozoites, including screening of compounds that would eliminate them, can only be made using common macaque models, principally Macaca rhesus and Macaca fascicularis, experimentally infected with the relapsing Plasmodium cynomolgi. Here, we present a protocol for long-term in vitro cultivation of P. cynomolgi–infected M. fascicularis primary hepatocytes during which hypnozoites persist and activate to resume normal development. In a proof-of-concept experiment, we obtained evidence that exposure to an inhibitor of histone modification enzymes implicated in epigenetic control of gene expression induces an accelerated rate of hypnozoite activation. The protocol presented may further enable investigations of hypnozoite biology and the search for compounds that kill hypnozoites or disrupt their quiescence.